More and sooner, but not necessarily better - Vichayavilas, Piyagarnt; Gist, Katja; Kaufman, Jon (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Critically ill children have generalized nutrition compromise. The timing of parenteral nutrition (PN) initiation has been under debate in both adults and children. A recent report of a multi-national randomized control trial in children demonstrated clinical superiority of delaying initiation of parental nutrition, and was associated with improved clinical outcomes and a lower rate of infection. In this editorial, we discuss our communication with the authors and our experience in a large cardiac intensive care unit (CICU) in the United States where improved nutrition delivery, and early PN, has improved weight-for-age z-score (WAZ) but has not shown any difference in length of hospital stay or reduced ventilator times.